1985
DOI: 10.1136/emj.2.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Do accident and emergency patients collect their prescribed medication?

Abstract: SUMMARYOne month's prescriptions from an accident and emergency department were examined. Of these 16% were found not to have been dispensed by the chemist. The commonest drugs prescribed were antibiotics (60%) and analgesics (22%). Most age groups were guilty of failing to collect drugs-primary non-compliance. METHODIn this department FP10 prescription forms are available for use by accident and emergency doctors at times when the hospital pharmacy is closed. The drugs are issued by the local dispensing chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The rate of prescription noncompliance for our pediatric population more closely resembles those observed in studies of adult ED patients. [20][21][22]30 Subtypes of ''insurance status,'' the only significant predictor identified through multivariable analysis in our study, have been previously shown to be associated to medication noncompliance in adult ED populations. 22 Guardians were considered noncompliant if prescribed medications were not obtained within two days of the ED visit.…”
Section: Discussionmentioning
confidence: 58%
“…The rate of prescription noncompliance for our pediatric population more closely resembles those observed in studies of adult ED patients. [20][21][22]30 Subtypes of ''insurance status,'' the only significant predictor identified through multivariable analysis in our study, have been previously shown to be associated to medication noncompliance in adult ED populations. 22 Guardians were considered noncompliant if prescribed medications were not obtained within two days of the ED visit.…”
Section: Discussionmentioning
confidence: 58%
“…The results are consistent with studies from EDs and nonpediatric primary care, showing rates of unfilled prescriptions ranging from 16% to 35% and 16% to 24%, respectively. [5][6][7][8]12,13 Our findings suggest that nondemographic factors, such as the method of prescribing (electronic versus paper), clinic site, medication This study did not show a significant association between child age and prescription filling. A previous study of 65 patients also found a lack of significant association, but it may have been too small to detect a difference.…”
Section: Discussionmentioning
confidence: 40%
“…Claims data for adult ED prescriptions demonstrate that 16% to 25% of prescriptions are not filled. [5][6][7] Studies from pediatric EDs demonstrate rates of unfilled prescriptions from 7% based on survey data 8 to 35% by using claims data. 9 Primary medication nonadherence also occurs in a primary care setting.…”
mentioning
confidence: 99%
“…Previous studies using pharmacy data to determine adult emergency department prescription fill rates showed rates ranging from 74-84%, 48,54,56 with one as low as 19.8%. 57 Since we only 36 looked at insured patients, it was expected that our fill rates would actually be higher than those seen previously.…”
Section: Discussionmentioning
confidence: 99%